Surprise for a princess - Weinberg, Jennifer, 1970- (New York : Random House, 2003)
The fairies Flora, Fauna, and Merryweather make a mess trying to surprise Briar Rose on her birthday, but their magic fixes things in the end.
Accelerated Reader AR
Keywords: Birthdays -- Fiction; Fairies -- Fiction; Magic -- Fiction